## Expanding and Simplifying (x+3)^2 - 5

This expression combines several mathematical concepts, including:

**Squaring a binomial:**We need to understand how to expand (x+3)^2**Order of operations:**We need to perform the operations in the correct order.

Let's break it down step-by-step:

### Expanding (x+3)^2

Remember that squaring a binomial means multiplying it by itself:

(x + 3)^2 = (x + 3)(x + 3)

To expand this, we can use the **FOIL** method (First, Outer, Inner, Last):

**First:**x * x = x^2**Outer:**x * 3 = 3x**Inner:**3 * x = 3x**Last:**3 * 3 = 9

Combining the terms:

(x + 3)^2 = x^2 + 3x + 3x + 9 = **x^2 + 6x + 9**

### Simplifying the Entire Expression

Now we can substitute this back into our original expression:

(x + 3)^2 - 5 = **x^2 + 6x + 9 - 5**

Finally, combine the constant terms:

**x^2 + 6x + 4**

### Conclusion

The simplified form of (x+3)^2 - 5 is **x^2 + 6x + 4**. This process involved expanding a binomial, applying the order of operations, and combining like terms.